Acute lymphoid leukemia cells with greater stem cell antigen-1 (Ly6a/Sca-1) expression exhibit higher levels of metalloproteinase activity and are more aggressive in vivo. - Yu-Chiao Hsu; Kurt Mildenstein; Kordell Hunter; Olena Tkachenko; Craig A Mullen (PLoS ONE)
Stem cell antigen-1 (Ly6a/Sca-1) is a gene that is expressed in activated lymphocytes, hematopoietic stem cells and stem cells of a variety of tissues in mice. Despite decades of study its functions remain poorly defined. These studies explored the impact of expression of this stem cell associated gene in acute lymphoid leukemia. Higher levels of Ly6a/Sca-1 expression led to more aggressive leukemia growth in vivo and earlier death of hosts. Leukemias expressing higher levels of Ly6a/Sca-1 exhibited higher levels of matrix metalloproteinases. The results suggest the hypothesis that the more aggressive behavior of Ly6a/Sca-1 expressing leukemias is due at least in part to greater capacity to degrade microenvironmental stroma and invade tissues.